Stability and Stabilization of Linear Parameter-Varying and Time-Varying Delay Systems with Actuator Saturation - Bui, Tuan Viet Long (The University of Picardy Jules Verne, 2022)
Chapter 1: General Introduction and Summary. Chapter 2: Overview Linear Parameter-Varying Systems. Chapter 3: Quadratic Stabilization Analysis for LPV/quasi-LPV Systems with Actuators Saturation...